Resilience and Return in Isaiah—Using Resilience Theory in Hebrew Scripture Theology - Klein, Anja (Religions, 2023)
The article analyses the theology of homecoming in the book of Isaiah and makes a case for using resilience theory as a hermeneutical frame for the task of Hebrew Scripture theology. Defined as “positive adaptation despite adversity”, resilience builds on the crisis setting of wide parts of the Hebrew Scriptures and demonstrates that the formation of theology represents a resilience discourse. In the case of the Isaianic prophecies of return, three concepts of return are distinguished (return, gathering and homecoming, a second Exodus) that respond to the adversities of exile and diaspora. Thus, the prophecies offer a literary home that the different religious communities through time can inhabit.